Circular Economy Integration in 1G+2G Sugarcane Bioethanol Production: Application of Carbon Capture, Utilization and Storage, Closed-Loop Systems, and Waste Valorization for Sustainability - Paul Latiza, Rich Jhon; Rubi, Rugi Vicente (Applied Science and Engineering Progress, 2025)
Bioethanol production is a vital player in the renewable energy landscape. However, it faces pressing issues regarding carbon emissions and resource management. Traditional open-loop systems generate substantial waste and pollution, exacerbating environmental concerns. Various emerging technologies offer promising solutions. Carbon Capture, Utilization, and Storage (CCUS) presents avenues for tackling carbon emissions. Utilization transforms CO2 emissions into valuable products, while Storage securely stores emissions to prevent atmospheric release. Closed-loop processes and waste valorization capitalize on material reuse, conserving natural resources, and minimizing waste. By promoting resource efficiency and waste minimization, circular economy principles align seamlessly with CCUS, closed-loop systems, and waste valorization. This study delves into utilizing Utilization technologies tailored to sugarcane 1G+2G bioethanol production, evaluates CO2 capture options, and presents applications. Storage strategies suitable for bioethanol production facilities are scrutinized, and deployment options are explored, highlighting the closed-loop system and waste valorization's role in waste reduction and environmental preservation. Through synergistic integration, these technologies pave the way for sustainable sugarcane bioethanol production, addressing economic and technological challenges while fostering innovation and collaboration. This comprehensive study will serve as a guide for transitioning to a circular economy model in bioethanol production.